المواد الدراسية على ضوء التدريبات الهرمية - Dzul Hanan (An Nabighoh Jurnal Pendidikan Dan Pembelajaran Bahasa Arab, 2017)
This article says on teaching matter and pyramid drill. The first is consist of teaching matter definition; its various; its selection standard; and its evaluation. The second is comprise with pyramid drill definition; its teaching steps; and its matter sample. From the data, so the research finding is the teaching matter base on pyramid drill.